Long term effectiveness of intraoperative radiotherapy given as a boost in adjuvant treatment for oral cavity cancers - Grzegorz Woźniak; Tomasz Rutkowski; Wojciech Majewski; Aleksandra Napieralska; Jerzy Wydmański; Agnieszka Czarniecka; Cezary Szymczyk; Adam Bekman; Żaneta Kaniszewska Dorsz; Tomasz Latusek; Bogusław Maciejewski (Scientific Reports)
Abstract The oral cancer treatment of choice is surgical excision with an organ preservation, if it is possible. Radiation therapy is commonly used as a postoperative treatment. Delivering radiation dose during surgery, defined as intraoperative radiotherapy (IORT), can be very useful especially in case of high risk of recurrence or where gross or macroscopic residual disease are present. The aim of this retrospective study is to evaluate the effectiveness of IORT combined with postoperative fractionated irradiation (EBRT) of patients with squamous cell carcinoma of the oral cavity. The study included 23 patients: IORT dose of 5–7.5 Gy was delivered using 50 kV X-rays generated by INTRABEAM™, combined with EBRT of 50–60 Gy in 25–30 fractions depending on presence of extracapsular invasion and narrow or positive surgical margins. Standard statistical tests were used. Median follow up was 64 months (range 8–222 months). The 5-year local tumour control was 92% and 82.5% in the 10-year follow-up. The 5-year overall survival (OS) was 56% and decreased to 45% during the next 5 years. There were no differences in the LTC, DFS and OS regarding sex, T-stage, grade and tumour localization, although a small group of analysed cases may raise some uncertainties. Acute side effects of combined IORT and EBRT were mild and no late complications occurred. The present study indicated that low-energy X-rays IORT combined with postoperative EBRT is a feasible and safe therapeutic modality which likely reduces a risk of locoregional recurrences.